(untitled) (JOURNAL OF ADVANCES IN AGRICULTURE, 2018)
The research was carried out in five different locations in 2010 and 2011 years under in the ecological conditions of Hayrabolu, Malkara, Suleymanpasa, sarköy and Saray district. Twenty-three bread wheat varieties were used as material in the study. the study carried out in the same area was made up of 2 different growing conditions, namely field conditions and a covered area covered with sunlight. The sunn pest damage rates in wheat varieties grown in the open area were ranged from of 6.0. to 0.10 %. The sunn pest damage rates in bread wheat varieties grown in closing area was changed between 10.37 to 23.17% with a significant increase. the average of the highest sunn pest damage in two years was observed the numbered 15, 10, 1, 11 and 16 cultivars, while the lowest values was obtained form 4, 13, 8 and 3 varieties According to the SDS-PAGE analysis in order to determine the genotypic differences of bread wheat varieties, protein band number in bread wheat varieties was ranged from 17 to 21, the density and molecular weight of protein bands were significant differences among the varieties. Protein bands are distributed predominantly in the omega region while in the gamma and beta regions a small number of bands were observed. There are no bands in bread wheat varieties in the alpha region.